How nuclear weapons spread : nuclear-weapon proliferation in the 1990s - Barnaby, Frank (Operational level of war., 1993)
Frank Barnaby examines the far-reaching effects - both beneficial and detrimental - of nuclear weapons, and looks in detail at the nuclear programmes of Third World countries, including India, Israel and Pakistan.